TENAGA KERJA WANITA DALAM PERSPEKTIF ISLAM - Amiroh Ambarwati (Muwazah, 2009)
Islam as a rahmatan lil ‘alamin religion (as a mercy for all creatures), gives genuine recognition and high appreciation of human equality. All human beings are equal, because they come from the same source, Allah Almighty. Human being can be distinguished to another by the level of his obidence and complience. As a logical consequence, each person (read: male or female) has the same obligations and responsibilty to fulfill and have the same rights to accept. Unfortunately, the essence of the equality doctrine is often biased when the understanding of Islam has been contaminated by the patriarchal mindset so that there are many different views about women’s status and position, which are considered as inferior to men. On the other hand, women who are initially claimed to occupy only domestic or household jobs, for example, they now have started reaching the public domain which was originally considered an unusual thing, consequently they must perform the dual roles as housewives and as workers. Along with the rise of the controvercy over women in these dual roles, this paper will attempt to review those roles of women from the religion’s point of view, especially how Islam regards the presence of female workers.